Application of Streptomyces sp. and Trichoderma sp. for Promoting Generative Plants Growth of Cherry Tomato (Lycopersicum cerasiformae Mill.) - Najvania Nawaal; Guniarti Guniarti; Ida Retno Moeljani; Penta Suryaminarsih (PLANTA TROPIKA, 2022)
Production of cherry tomatoes in Indonesia is still low, which might be due to the inappropriate planting and maintenance processes. This research applied biological agent microorganisms Streptomyces sp. and Trichoderma sp. as Plant Growth Promoting Microorganisms (PGPM) in sustainable agricultural systems. This study aimed to determine the effect of the concentration of microorganisms Streptomyces sp. and Trichoderma sp. on the growth and production of cherry tomato plants on the polybag scale. The study was arranged with different concentrations of microorganisms Streptomyces sp. and Trichoderma sp. These concentration applied consisted of 1 : 0 ; 0 : 1 ; 2: 2 ; 3 ; 1 and without PGPM, each repeated four times. The results showed that the treatment of PGPM Streptomyces sp. and without Trichoderma sp. (1:0) resulted in the shortest flowering period (33.99 days after planting). Meanwhile, the treatment without Streptomyces sp. and Trichoderma sp. (0 : 1) produced the highest solid weight fruit (69.82 grams/plant).